Space and Intermediality in Jia Zhang-ke’s Still Life - Mello, Cecília (2014)
This article is dedicated to an analysis of Chinese director Jia Zhang-ke’s film Still Life (San Xia Hao Ren 三峡好人, 2006) from the point of view of its intermedial relationship with Chinese landscape painting. As I will suggest, Jia’s discovery of a real landscape and a vanishing cityscape in this film, shot on location in the region of the Three Gorges of the Yangtze River, springs from a realist impulse and from an original aesthetic response to a new historical and social conjuncture. But while it seems firmly located in the landscape of contemporary China, the film also shares aesthetic qualities with the tradition of Chinese landscape painting, mounted on hanging or hand scrolls. A focus on this particular instance of intermediality leads to a reflection on cinema’s spatial organization in light of current revisions in film and audiovisual theory, which suggest that filmic space and its spectatorial experience should be considered above all from the point of view of touch and movement. It also allows for a broader understanding of the political implications of intermediality in Jia Zhang-ke’s oeuvre, fruit of an organic link between form and content that brings a historical resonance to a contemporary perspective.